Phytolith assemblages from palm leaves and palm-leaf manuscripts: what is the difference and what it could mean? - Poliakova, Anastasia; Ciotti, Giovanni; Helman-Wazny, Agnieszka; Fromm, Jörg (Frontiers in Plant Science, 2025)
We studied freshly collected, dried and herbarized leaf fragments of two palms, namely Borassus flabellifer L. and Corypha umbraculifera L., most commonly used for palm-leaf manuscript (PLM) production in South (S) and Southeast Asia (SE) in order to reveal differences in their phytolith assemblages. For each of the two palms, 25 leaf samples were taken from the two Indian states of Kerala and Tamil Nadu. Dried leaf material was obtained from the fresh one by drying the leaves in air. Herbarium samples were obtained from two independent herbaria, specimen origin comprises S and SE Asia with the main focus on South India and Sri Lanka. Additionally, 25 manuscripts made of Borassus flabellifer leaves and 25 manuscripts made of Corypha umbraculifera leaves were investigated for phytoliths. All manuscripts are preliminary dated back to between the 16th and the beginning of the 20th century CE; most of them assumedly were produced in S India (Tamil Nadu and Kerala), Sri Lanka, Burma or Indonesia. Phytolith assemblages significantly differed between fresh, dry and herbarized palm leaves in comparison to PLM material, both qualitatively and quantitatively (mean r2 = - 0.61 ± 9.3 for Borassus samples and r2 = - 0.75 ± 5.3 for Corypha samples, at p < 0.001). Fifty-three phytolith types described for PLM material were not observed in any of the fresh, dry or herbarized palm-leaf samples. Geographical analysis of PLM-specific phytoliths suggests that the combination of those phytoliths could be region-related. In this paper, we prove that the methods of palaeoecological reconstructions based on detailed microscopy of the PLMs surface and phytolith analysis applied in combination with methods of mathematical and computer data analysis can contribute to answer the questions posed by material codicology by revealing lost manuscript production recipes and by studying manuscript provenance in terms of the geographical origin of the artefacts. Our approach can potentially open a new perspective for palaeoecological studies expanding their traditional scope and making them applicable to a new research field.